The efforts of power: political and economic game in the contracting of the contract of entries in Royal Treasury Board in the captaincy of Minas Gerais by Joaquim Silverio dos Reis (1781) - Rodrigues, Andre Figueiredo [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2023)
This text aims to analyse, in the context of the contracting of income and royal monopolies in the captaincy of Minas Gerais, during the 18th century, as occurred the process of auctioning the contract of entry for the period from January 1, 1782 to December 31, 1784, by Joaquim Silverio dos Reis, known in history as one of the whistleblowers of the Inconfidencia Mineira (1789-1792). To this end, at first, the discovery of gold and the consequences of this act in the territory of the captaincy of Minas Gerais and the implementation of the tax regime in that area; then, we present a brief discussion on the general characteristics of the tax system and the administration of contracts in 18th century Minas Gerais; and hence its historiographical context; finally, the political and economic game that caused Silverio dos Reis to win the contract of entries before the Royal Treasury Board in November 1781.
Keywords: Silverio dos Reis; Royal monopoly contracting; Contract of entries; Royal Treasury Board; Captaincy of Minas Gerais; second half of the eighteenth century